Nomenclatural availability of nomina of new species should always require the deposition of preserved specimens in collections: a rebuttal to Donegan (2008) - Nemésio, André (Zootaxa, 2009)
Recently, a paper (Dubois & Nemésio 2007) expressed general views regarding the deposition of vouchers in public collections to serve as onomatophores (name-bearing type specimens), and it was suggested that deposition should be made explicitly compulsory in the Code, to avoid the growing number of descriptions that skip this process opportunistically based on some apparent ambiguities of the Code. Donegan (2008) made several criticisms to that paper, defending a “liberal approach” of the Code concerning the nature of type specimens. Here I present my rebuttal to Donegan (2008), showing point by point that his criticisms are the sum of misunderstandings of the Code and of the ideas presented in Dubois & Nemésio (2007), allied to some biased and very subjective personal interpretations. The arguments used to allow description without the deposition of voucher(s) are once more demonstrated to be based on articles of the Code that do not serve to this end and the suggestions of amendment of the Code presented by Dubois & Nemésio (2007) are shown to adequately accommodate the concerns of conservationists regarding descriptions of species found on the brink of extinction.